The Transliteration and Translation of the Leiden Manuscript Cod. Or. 5626 on the Sijill of the Qadi of Banten 1754-1756 CE. - Yakin, Ayang Utriza (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2016)
The article provides the critical edition of the Leiden Manuscript Cod. Or. 5626. It gives the transliteration from the pegon (Javanese in modified-Arabic letters) into the Latin letter and the translation from Javanese into English. The publication of this edition is intended to reach a wider reader, especially to the philologist and scholars in Islamic law, in order to have an access to the original text. It should serve a precious source for those who are interested in Islamic legal history. This is the oldest and the first register of qadi ever known from Southeast Asia. The paper contributes tremendously to the field of Islamic law and Southeast Asian studies.